Review of the Completeness of Filling Out the Medical Procedure Consent Form (Informed Consent) for Inpatient Surgical Patients at Dr. Soedirman Regional General Hospital Kebumen - Rizqy Azhar , Ananda; Diansyah, Diansyah (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
The informed consent form is a mandatory legal document that must be completed before any medical procedure, especially surgical interventions. The completeness of informed consent is essential to ensure patient safety, fulfill ethical standards in healthcare services, and provide legal protection for both medical personnel and hospitals. In practice, however, incomplete informed consent documentation is still frequently found, which may reduce the quality of medical records and increase the risk of medico-legal disputes. To determine the completeness of informed consent documentation for inpatient surgical patients at RSUD Dr. Soedirman Kebumen and to identify the components most frequently left incomplete. This study employed a quantitative descriptive design with a sample of 118 inpatient surgical medical records. Data were collected using an observation checklist based on key informed consent components, including patient identity, attending physician’s signature, clarity of procedure information, and date and time of consent. The data were analyzed descriptively by calculating the frequency and percentage of completeness for each component. Of the 118 records analyzed, 90 records (76.3%) were categorized as complete, while 28 records (23.7%) were incomplete. The highest rate of incompleteness was found in the clarity of procedure information component, with 24 incomplete records (20.3%). The attending physician’s signature was incomplete in 12 records (10.2%). Meanwhile, patient identity and date and time components each showed 3 incomplete records (2.5%). The completeness of informed consent documentation for inpatient surgical patients at RSUD Dr. Soedirman Kebumen is categorized as adequate but does not yet meet the ideal standard (≥90%). The components most frequently incomplete were clarity of procedure information and attending physician’s signature. Improvements in healthcare personnel compliance, document format refinement, and strengthened verification systems are necessary to enhance the quality of informed consent documentation.